Hair mercury concentrations among Pakistani city dwellers: Use of personal care products as a source of variation - Kanwal, Sadia; Yoshinaga, Jun (Biomedical Research on Trace Elements, 2019)
In many countries, regulations requiring the monitoring of human mercury exposure levels are becoming increasingly stringent. In this study, mercury exposure among Pakistani city dwellers was assessed by means of hair mercury analysis. Specifically, we used cold-vapor atomic absorption spectrometry to measure hair mercury concentrations in 291 adult subjects (136 males and 155 females) residing in 6 major cities of Pakistan. A questionnaire was used to obtain information about biological and lifestyle characteristics of the subjects. Most of the subjects had low hair mercury concentrations (median, 0.35 μg/g) and were therefore not at significant health risk due to mercury exposure; however, some subjects had excessive hair mercury concentrations (up to 565 μg/g). The use of skin creams and soaps was found to be a major contributor to excessive hair mercury concentration. In addition, among the subjects who did not have excessive hair mercury concentrations, frequency of fish consumption, smoking, city of residence, and education level were also minor but statistically significant contributors to hair mercury concentration. Our results suggest that the use of mercury-containing personal care products (particularly skin creams and soaps) among Pakistani city dwellers was the main significant source of exposure to mercury.